Análisis de los procesos y procedimientos para la optimización de tiempos de ingreso de mercancías amparadas bajo el régimen de transito aduanero (2022)
The objective of this document is to make a proposal to efficiently adjust the processes and procedures for the optimization of entry times of goods covered under the Customs Transit regime of cargoes from the customs of Bogotá, Buenaventura, Cali, Cartagena and Ipiales to the Pacific Free Zone. Therefore, a case study is carried out, compiling information from the period 2018 - 2021 and applying a survey directed to the officials of the user operator of the Pacific Free Zone and the officials of the Internal Transit Group (GIT) of the tax and customs department. The most relevant inconsistencies are identified, such as badly related plate in customs transit, wrong seals, system does not generate entry notice, because it does not have port exit notice. This research results in a proposal that helps to better optimize the time of entry of customs transits to the Pacific Free Zone, where 3 aspects are taken into account: 100% digital process, adjustment of the functions of Dian officials and reduce the boxes of the document (Duta) that are not relevant.